Green Capabilities and Corporate Competitive Advantage: The Moderating Effect of Green Culture - Erna Wati; Jesslyn Jesslyn; Sheila Septiany (Studi Akuntansi, Keuangan, dan Manajemen, 2026)
Purpose: This study aims to examine the influence of Green Intellectual Capital (GIC), Green Leadership (GL), Green Human Resource Management (GHRM), and Green Organizational Learning Capability (GOLC) on Corporate Competitive Advantage (CCA), with a particular focus on the moderating role of Green Culture (GC) in strengthening these relationships. Methodology/approach: This study uses a quantitative approach with an online survey conducted among 163 key decision-makers from listed companies practicing sustainability. Data were analyzed using PLS-SEM to test the research hypotheses. Results/findings: The findings indicate that GIC, GL, GHRM, and GOLC exert a significant positive influence on CCA. Moreover, GC strengthens these relationships as a moderating factor, although variations across variables suggest the influence of other organizational factors. Conclusions: This study concludes that GL, GHRM, and GOLC significantly enhance CCA, while GIC shows no direct effect. Moreover, GC strengthens the relationships between GL and GOLC with CCA, highlighting the importance of a sustainability-oriented culture in driving competitive performance. Limitations: This study is limited to Indonesian companies and relies solely on quantitative survey data, which may not fully capture the depth of green management practices. Future research could explore cross-country comparisons or adopt a mixed-method approach for deeper insights. Contribution: This study contributes to the field of green strategic management by emphasizing the role of GC in enhancing sustainability performance. It provides valuable guidance for companies and policymakers aiming to embed environmental values into organizational strategies.